Penerapan Standar Kompetensi Sante Per Aqua (Spa) pada Pelayanan Home Spa di Kota Padang - Novaldi, Haura; Yupelmi , Mimi (Journal of Beauty and Cosmetology (JBC), 2024)
This study aims to analyze the application of massage procedures, the application of K3 (Occupational Safety and Health) and how therapists communicate at home SPA in Padang City. This type of research is descriptive quantitative. The population of this study was 14 therapists and owners of SPA homes in Padang City. The sampling technique is Total Sampling with a total of 14 people. Data collection using questionnaires (questionnaires) adjusted in the form of Likert scales. Data analysis techniques use descriptive quantitative data analysis tests and data analysis of respondent achievement level (TCR) calculations. The results of the study based on the level of achievement of respondents (TCR) stated that 78% with the category of good enough therapist home SPA have carried out massage procedures in accordance with the principles of SKKNI SPA, 84% with the category of good therapist home SPA have done how to communicate in accordance with the principles of SKKNI SPA, 78% with the category of good enough therapist home SPA has done Occupational Safety and Health (K3) in accordance with the principle of K3 in SKKNI SPA. Berdasarkan hasil penelitian ini disarankan dapat digunakan sebagai informasi mengenai Penerapan Standar Kompetensi SPA pada Pelayanan Home SPA dan dapat menjadi referensi atau bahan pertimbangan untuk meningkatkan kualitas penerapan standar kompetensi SPA pada pelayanan home SPA terutama yang ada di Kota Padang. Based on the results of this study, it is suggested that it can be used as information about the Application of SPA Competency Standards in SPA Home Services and can be a reference or consideration to improve the quality of the application of SPA competency standards in SPA home services, especially those in Padang City. Keywords: Applicability, Competency Standards, SPA, Home SPA